Characteristics of current digital single-use flexible ureteroscopes versus their reusable counterparts: an in-vitro comparative analysis - ŞENER, TARIK EMRE (AME PUBL CO, 2019)
Background: Single-use flexible ureterorenoscopes (fURSs) have been recently introduced aiming to offer solutions to the sterilization, fragility and cost issues of the reusable fURSs. In order to be a viable alternative, the single-use scopes must prove similar capabilities when compared to their reusable counterparts. The goal of our in-vitro study was to compare the current reusable and single-use digital fURSs regarding their deflection, irrigation and vision characteristics. Methods: We compared in-vitro 4 single-use fURSs-LithoVue (TM) (Boston Scientific, Marlborough, Massachusetts, USA), Uscope (TM) (Zhuhai Pusen Medical Technology Co. Ltd., Zhuhai, Guangdong Province, China), NeoFlex (TM) (NeoScope Inc, San Jose, California, USA) and ShaoGang (TM) (YouCare Technology Co. Ltd., Wuhan, China) versus 4 reusable fURSs-FLEX-Xc (Karl Storz SE & Co KG, Tuttlingen, Germany), URF- V2 (Olympus, Shinjuku, Tokyo, Japan), COBRA vision and BOA vision (Richard Wolf GmbH, Knittlingen, Germany). Deflection and irrigation abilities were evaluated with different instruments inserted through the working channel: laser fibres (200/273/365 mu m), retrieval baskets (1.5/1.9/2.2 Fr), guide wires [polytetrafluoroethylene (PTFE) 0.038 inch, nitinol 0.035 inch] and a biopsy forceps. A scoring system was designed to compare the deflection impairment. Saline at different heights (40/80 cm) was used for irrigation. The flow was measured with the tip of the fURS initially straight and then fully deflected. The vision characteristics were evaluated (field of view, depth of field, image resolution, distortion and colour representation) using specific target models. Results: Overall, the single-use fURSs had superior in-vitro deflection abilities than the reusable fURSs, in most settings. The highest score was achieved by NeoFlexT and the lowest by ShaoGang (TM). PTFE guide wire had most impact on deflection for all fURSs. The 200 mu m laser fibre had the lowest impact on deflection for the single-use fURSs. The 1.5 Fr basket caused the least deflection impairment on reusable fURSs. At the end of the tests, deflection loss was noted in most of the single-use fURSs, while none of the reusable fURSs presented deflection impairment. ShaoGang (TM) had the highest irrigation flow. Increasing the size of the instruments occupying the working channel led to decrease of irrigation flow in all fURSs. The impact of maximal deflection on irrigation flow was very low for all fURSs. When instruments were occupying the working channel, the single-use fURSs had slightly better in-vitro irrigation flow than the reusable fURSs. The field of view was comparable for all fURSs, with LithoVue (TM) showing a slight advantage. Depth of field and colour reproducibility were almost similar for all fURSs. ShaoGang (TM) and UscopeT had the lowest resolution. FLEX Xc had the highest image distortion while LithoVueT had the lowest. Partial field of view impairment was not for Uscope (TM) and ShaoGang (TM). Conclusions: In-vitro, there are differences in technical characteristics of fURSs. It appears that single-use fURSs deflect better than their reusable counterparts. Irrespective of deflection, the irrigation flow of the singleuse fURSs was slightly superior to the flow of the reusable fURSs. Overall, reusable fURSs had better vision characteristics than single-use fURSs. Further in-vivo studies might be necessary to confirm these findings.
Keywords: Single-use; reusable; digital flexible ureteroscopes; STONE DISEASE; ROBOFLEX AVICENNA; OUTCOMES; URETERORENOSCOPY; LITHOVUE(TM); TRENDS